Deciphering fungicide resistance in Phytophthora: Mechanisms, prevalence, and sustainable management approaches. - Syed Atif Hasan Naqvi; Muhammad Farhan Syakir Nor Azman; Muhammad Ahmad; Rafa Kiran; Noor Fatima; Muhammad Shahbaz; Muhammad Akram; Jaya Seelan Sathiya Seelan; Amjad Ali; Salman Ahmad (Springer nature link, 2024)
The genus Phytophthora contains more than 100 plant pathogenic species that parasitize a wide range of plants, including economically important fruits, vegetables, cereals, and forest trees, causing signifcant losses. Global agriculture is seriously threatened by fungicide resistance in Phytophthora species, which makes it imperative to fully comprehend the mechanisms, frequency, and non-chemical management techniques related to resistance mutations. The mechanisms behind fungicide resistance, such as target-site mutations, efux pump overexpression, overexpression of target genes and metabolic detoxifcation routes for fungicides routinely used against Phytophthora species, are thoroughly examined in this review. Additionally, it assesses the frequency of resistance mutations in various Phytophthora species and geographical areas, emphasizing the rise of strains that are resistant to multiple drugs. The efectiveness of non-chemical management techniques, including biological control, host resistance, integrated pest management plans, and cultural practices, in reducing fungicide resistance is also thoroughly evaluated. The study provides important insights for future research and the development of sustainable disease management strategies to counter fungicide resistance in Phytophthora species by synthesizing current information and identifying knowledge gaps.